2008
DOI: 10.1002/ar.20738
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Myocardial and Coronary Vasculature Development in Experimental Hypoxia

Abstract: Oxygen availability is one of the necessary prerequisites for normal embryonic development. In our previous study we found that quail embryos incubated under hypoxic conditions (16% O 2 ) die at embryonic day (ED) 9 with signs of heart failure. By ED4 and ED6 we found thinner ventricular wall and increased capillary density. We thus hypothesized that the cause of death would lie in severe myocardial and coronary maldevelopment. ED6 and 7 hypoxic hearts had thinner ventricular wall, especially left. There was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 48 publications
(54 reference statements)
1
14
0
Order By: Relevance
“…Experimental studies have demonstrated that reduced fetal oxygen supply causes incomplete development of the heart, like ventricular septal defects, myocardial thinning, ventricular dilatation, and epicardium detachment, and slows fetal heart maturation (Sharma et al 2006;Ream et al 2008;Nanka et al 2008). In fetal sheep, long-term hypoxemia (natural altitude 3820 m a.s.l., 110 days) reduced cardiac output and contractility (Gilbert 1998), increased lactate dehydrogenase and citrate synthase (Ohtsuka and Gilbert 1995), and resulted in cardiomegaly (Murotsuki et al 1997;Martin et al 1998).…”
Section: Hypoxia and The Fetal Mammalian Heartmentioning
confidence: 98%
“…Experimental studies have demonstrated that reduced fetal oxygen supply causes incomplete development of the heart, like ventricular septal defects, myocardial thinning, ventricular dilatation, and epicardium detachment, and slows fetal heart maturation (Sharma et al 2006;Ream et al 2008;Nanka et al 2008). In fetal sheep, long-term hypoxemia (natural altitude 3820 m a.s.l., 110 days) reduced cardiac output and contractility (Gilbert 1998), increased lactate dehydrogenase and citrate synthase (Ohtsuka and Gilbert 1995), and resulted in cardiomegaly (Murotsuki et al 1997;Martin et al 1998).…”
Section: Hypoxia and The Fetal Mammalian Heartmentioning
confidence: 98%
“…Effects of hypoxia on heart development were more directly addressed in quail embryos incubated under hypoxic conditions (16% oxygen) (Nanka et al, 2008). Their studies demonstrated thin ventricular walls developed and irregularities were observed in the development of the coronary tree.…”
Section: Animal-based Hemodynamic Studies Carried Out On Vitelline Anmentioning
confidence: 99%
“…The base of the aorta expresses the hypoxia-induced transcription factor Hif1α, whose expression in chick is induced in response to hypoxia and correlates with coronary ostium placement (Wikenheiser et al, 2009). Exposing quail embryos to hypoxia increases the capillary density throughout the myocardium, consistent with low oxygen levels promoting vascular growth (Nanka et al, 2008). When quail embryos are placed in a hypoxic environment at approximately Hamburger-Hamilton stage 12 (after 48 h of incubation), atretic coronary arteries are observed (Nanka et al, 2008).…”
Section: Hypoxia-induced Signaling During Coronary Stem Formationmentioning
confidence: 90%
“…Exposing quail embryos to hypoxia increases the capillary density throughout the myocardium, consistent with low oxygen levels promoting vascular growth (Nanka et al, 2008). When quail embryos are placed in a hypoxic environment at approximately Hamburger-Hamilton stage 12 (after 48 h of incubation), atretic coronary arteries are observed (Nanka et al, 2008). In contrast, exposing chick embryos to either hypoxic or hyperoxic conditions starting at Hamburger-Hamilton stage 25 (or approximately 4.5–5 days of incubation) does not cause coronary atresia but does lead to both anomalous origins of the coronary stems and additional stems (Wikenheiser et al, 2009).…”
Section: Hypoxia-induced Signaling During Coronary Stem Formationmentioning
confidence: 90%
See 1 more Smart Citation